Water and nutrient management in natural and constructed wetlands - Vymazal, Jan (Springer, 2010)
This book provides results of the latest research in wetland science around the world. Chapters deal with such topics as the use of constructed wetlands for treatment of various types of wastewater, use of constructed wetlands in agroforestry, wetland hydrology and evapotranspiration, the effect of wetlands on landscape temperature, and chemical properties of wetland soils.